Population-Based Estimates of SARS-CoV-2 Seroprevalence in Houston, Texas as of September 2020. (29th April 2021) - Symanski, Elaine; Ensor, Katherine B; Piedra, Pedro A; Sheth, Komal; Caton, Kelsey; Williams, Stephen L; Persse, David; Banerjee, Deborah; Hopkins, Loren
Abstract: Background: In contrast to studies that relied on volunteers or convenience sampling, there are few population-based severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) seroprevalence investigations and most were conducted early in the pandemic. The health department of the fourth largest US city recognized that sound estimates of viral impact were needed to inform decision making. Methods: Adapting standardized disaster research methodology, in September 2020 the city was divided into high and low strata based on reverse-transcriptase polymerase chain reaction (RT-PCR) positivity rates; census block groups within each stratum were randomly selected with probability proportional to size, followed by random selection of households within each group. Using 2 immunoassays, the proportion of infected individuals was estimated for the city, by positivity rate and sociodemographic and other characteristics. The degree of underascertainment of seroprevalence was estimated based on RT-PCR–positive cases. Results: Seroprevalence was estimated to be 14% with near 2-fold difference in areas with high (18%) versus low (10%) RT-PCR positivity rates and was 4 times higher compared to case-based surveillance data. Conclusions: Seroprevalence was higher than previously reported and greater than estimated from RT-PCR data. Results will be used to inform public health decisions about testing, outreach, and vaccine rollout. Abstract : In a population-based investigation, SARS-CoV-2 seroprevalence in Houston, TX was nearly 14% as of September 2020 with a near 2-fold difference in areas with high versus low RT-PCR positivity rates and was 4 times higher compared to case-based surveillance data.